Desafíos en la democratización de la educación técnica brasileña - Alan Jhone Carvalho de Araújo; Carolina Yukari Veludo Watanabe (Universidade Federal de Rondônia, 2019)
The democratization of technical education has suffered from the constant opening and closing of courses, as well as by the high number of students dropping out, negatively impacting the public purse. Thus, the goal was to identify the challenges of the educational process faced by the technical courses. As methodology, an integrative literature review was performed. For this, Scielo, EBSCO and Web of Science databases were used and a total of 21 articles were filtered and analyzed. As a result, challenges were encountered by students, teachers and educational institutions. As for the students, the challenges were the choice of the course, deficiency of previous education, difficulties in basic education and personal problems. For teachers, the challenges are related to career, with low salary and excessive workload, and teacher training, with the need for pedagogical training for bachelors and experience in the profession practice by graduates. Educational institutions have challenges regarding infrastructure, pedagogical projects of courses that do not adequately integrate theory and practice, offering and implementing courses in a period not suitable for the target audience. All these factors influence the pedagogical practice as well as the quality of education and the well democratization of education.